SCAFFOLDING THE LEARNING OF PROGRAMMING USING LEGO MINDSTORMS EV3 - Tengku Farah Hanum Nor, Tengku Mohd Noor (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examined the effect of Lego Mindstorms EV3 on learners’ problem solving and computational thinking scales, and its impact on their motivation and interest in computer programming. An intervention using Lego Mindstorm EV3 is conducted on 10 first year students of Cognitive Science. Problem Solving Survey (PSS) and Computational Thinking Test was used to measure students’ pre and post-test scores. The pre and post-test scores was analyzed using paired sample T-test. To measure the impact of EV3 on the students’ motivation and interest, a focus group interview was conducted. It is found that there’s a significant increase between the pre and post test for both tests. For problem solving scores, there was a significant difference in the scores for pretest (M = 65.6, SD = 5.87) and posttest (M = 68.0, SD = 6.32); t(9) = -3.88, p = .004. For computational thinking scores, there was a significant difference in the scores for pretest (M = 66.2, SD = 7.63) and posttest (M = 70.0, SD = 9.15); t(9) = -4.13, p = .003. EV3 give positive impact on the learning experience. Before the intervention, majority of the participants had negative mindsets on programming, in general (Refer Table ). These mindsets affected their motivation and interest in learning, thus, making it hard for them to learn. However, we can see from both observations during the sessions and the responses from post-intervention interview, that the mindset and behavior of the students had changed positively (Refer Table). The participants enjoyed the learning process. Thus, we can say that motivation factor should not be undervalued in educational process. Motivated learners often achieve more than unmotivated learners (Chetty, 2015).